STUDENT AGENCY IN AI-POWERED LEARNING ENVIRONMENTS: EMPOWERING LEARNERS THROUGH TECHNOLOGY - Pitriyani Mobiliu; Ava Lee; Kasim Yahiji (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2026)
The integration of Artificial Intelligence (AI) in education is reshaping how students interact with learning materials and take control of their educational journeys. AI-powered learning environments promise to enhance student agency by providing personalized learning experiences and immediate feedback. However, the impact of AI on student autonomy and the teacher-student dynamic remains underexplored. This study aims to investigate how AI technologies influence student agency in learning environments and how these tools empower learners to become more self-directed. A mixed-methods approach was employed, using surveys, interviews, and classroom observations across 10 schools that have adopted AI tools for learning. The results reveal that AI-powered tools significantly enhance student engagement and learning outcomes by offering personalized content, yet students expressed concerns about reduced opportunities for collaboration and human interaction. Teachers observed increased autonomy in students, but some raised concerns about AI’s potential to depersonalize the learning experience. The study concludes that while AI can effectively empower students, it is essential to strike a balance between the technological benefits and the need for human connection in the learning process. AI should complement, not replace, traditional pedagogical practices to foster a more holistic educational experience.